Statistical Comparison of Two Liquid Chromatographic Methods for Ritonavir in Tablets - Behera, Anindita; G. Sankar, Dannana; K. Moitra, Swapan; C. Si, Sudam (Asian Journal of Chemistry, 2013)
Two high performance liquid chromatography (HPLC) methods were developed for quantitation of ritonavir in raw material and tablet dosage form. The methods were validated and statistically compared. Both methods are carried out in a C18 column using the PDA detector at 240 nm. The first method, method A is carried out using methanol: acetonitrile: water in the ratio 87:10:3 (v/v/v) as mobile phase at a flow rate of 1 mL/min. The second method, method B is carried out using acetonitrile:methanol:buffer (pH = 6.2 ± 0.05) in the ratio 60:20:20 (v/v/v) as mobile phase at 1 mL/min. Both methods were validated according to ICH guidelines, showed good accuracy, precision, linearity and sensitivity. Two way anova and student's t-test was used to correlate the two methods and applied to raw materials and tablet dosage form. There was no significant difference between the two methods.